E-procurement dalam Pengadaan Barang dan Jasa untuk Mewujudkan Akuntabilitas di Kota Yogyakarta - UDOYONO, KODAR (Universitas Muhammadiyah Yogyakarta, 2012)
This research studied on implementation of stocking goods and services electricly. E-Procurement is abreaktrough in public services to create accountability on stocking of goods and services. The object ofwhich observed are stocking goods and services electricly at Yogykarta Municipality 2009. Thisresearch uses a case study method. The data obtained pass trough depth interview and documentobservation. The result of this research i.e Firstly, dimension fo ficibility in stocking of goods andservices electricly at Yogyakarta Municipality 2009 pass trough regulative, administrative andtechocratic, political, and needs society. Secondly, dimension of accountability on stocking of goodsand services electricly at Yogyakarta Municipality 2009 pass trough regulative, political, andfinancial. Finally, implementation e-procurement at Yogyakarta Municipality 2009 is ficible but noaccountable .